Theimpact of Adopting international Accounting Standards on the Kuwait Environment :The Perspective of Accountants ,Auditors and Acdemicians - Talal El- Jajawy; Ali abdelghani al-layth; Malek Al-Sharairy (Iraqi Journal for Administrative Sciences, 2025)
This research aims to examine the agreement extent of accounting policies that the Kuwait companies applied for measuring and evaluating the financial components with international accounting standards requirements, and the degree of application mastery between the companies, besides to examine the convenience of international accounting standards application in this in this connection. Accounting is practicing as one of the social sciences for the activities concerning the identifying, measuring and information communicating about the economic entities to other parties to facilitate the process of decision-making. The producing and communicating accounting information give a significant important to the roll of accounting, both on the micro and macro level, to increase the efficiency of the information in the economic decision-making by the parties who use the information. Accounting as a social science, its production functions, affects and to be affected by the environment which is surrounded these functions. Accounting profession has developed over ages to escort the develop of the modern societies, thus the developing become clear through the establishment of the professional bodies and societies around the world. As the importance of accounting as business language, it became pressing to unification this language between different countries, the international accounting standards committee (IASC) has stand alone to achieve this task through a chain of standards which govern the companies financial statements preparation.